2003
DOI: 10.4269/ajtmh.2003.68.350
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pfcrt, Pfmdr1, Dhfr, and DHPS Mutations and Drug Sensitivities in Plasmodium Falciparum Isolates From Patients in Vietnam Before and After Treatment With Artemisinin

Abstract: Abstract. We have analyzed artemisinin sensitivity in Plasmodium falciparum isolates obtained from patients in South Vietnam and show that artemisinin sensitivity does not differ before and after drug treatment. There was an increase in the level of mefloquine resistance in the isolates after drug treatment that was concomitant with a decrease in chloroquine resistance, suggesting that treatment with artemisinin has selected for increased mefloquine resistance. Mutations in the pfmdr1 gene, previously shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 39 publications
3
48
0
Order By: Relevance
“…In vivo resistance to QN was confirmed by an in vitro test and by molecular identification of an mdr1 Tyr-86 point mutation. The direct correlation between the presence of that mutation and QN resistance has been reported by Duraisingh et al (1), although it is not consistently found (7,9). As expected, in vitro testing showed CQ resistance, in line with the presence of mutated alleles at codons 76 and 220 of the pfcrt gene.…”
Section: Vol 42 2004 Case Reports 5425mentioning
confidence: 79%
“…In vivo resistance to QN was confirmed by an in vitro test and by molecular identification of an mdr1 Tyr-86 point mutation. The direct correlation between the presence of that mutation and QN resistance has been reported by Duraisingh et al (1), although it is not consistently found (7,9). As expected, in vitro testing showed CQ resistance, in line with the presence of mutated alleles at codons 76 and 220 of the pfcrt gene.…”
Section: Vol 42 2004 Case Reports 5425mentioning
confidence: 79%
“…Wild-type N86 allele in Pfmdr1 has been found with increased tolerance to both artemether and lumefantrine separately. [52][53][54] Moreover, the presence of N86 wild-type allele is a probable factor in the development of resistance against lumefantrine, and frequency of this allele varies according to different malarial transmission settings. 55,56 Pfmdr1 Y184F allele has either minor impact on drug response or weaker association with antimalarial effectiveness as compared with N86Y mutation, and expression of wild-type or mutant allele in codon 184 primarily depends on codon 86 status, class of drug to which parasite expose and genetic background of Pfcrt gene.…”
Section: Discussionmentioning
confidence: 99%
“…Since the site of the Cambodian study was within close proximity to our study site, these isolates may have been generated by low-level clonal spread across these areas. In Vietnam, Ngo (14).…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, chloroquine-resistant P. falciparum was reported for the first time in the 1960s (12,14). Ngo et al reported in 2003 that all of the isolates acquired from 18 adult rubber plantation workers residing in southern Vietnam demonstrated the pfcrt 76T mutation (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation